Adapting the DIPLOMACY Board Game Concept for 21st Century International Relations Teaching. (December 2018) - Mattlin, Mikael
Background. This article reports on pedagogical experiences of designing and teaching anactive learning international relations (IR) course utilizing the classical board game DIPLOMACY, withadded game elements andmodified game rules to make the game better suited for educational purposes. Aim. Game adaptations includeteam play, a dedicatedpeace mediator team, altered win rules and a post-gamedebriefing discussion on differentcultures of anarchy . These elements were designed to overcome a shortcoming that the game approximates a worldview akin to offensive realism, which is not practical in contemporary international relations, and also normatively objectionable to many IR scholars. Method. Teacher experiences designing and modifying the course, coupled with student feedback on the course concept from three consecutive years. Results. Student feedback has been exceedingly positive, with a 4.61 average grade (n = 210 grades) on a five-point Likert-type scale, where 1 signifies poor and 5 excellent . Conclusions. Through game modifications, students turned a game infamous for its backstabbing and breaking of promises into a game that resolves in a mediated and negotiated outcome. The findings suggest that DIPLOMACY can be useful beyond teaching the realist worldview, and adapted to create amore accurate microworld approximation of international relations.